Towards an assessment of psychosocial work factors in a multi-level mental health intervention in the workplace: results from the MENTUPP pilot-study - Fotini Tsantila; Reiner Rugulies; Evelien Coppens; Hans De Witte; Ella Arensman; Abdulla Kahar; Arlinda Cerga-Pashoja; Paul Corcoran; Lars De Winter; Birgit Greiner; Eve Griffin; Bridget Hogg; et al. (International Archives of Occupational and Environmental Health, 2024)

Correction: Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)

Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)
Objective Multicomponent interventions are recommendable to achieve the greatest mental health benefits, but are difficult to evaluate due to their complexity. Defining long-term outcomes, arising from a Theory of Change (ToC) and testing them in a pilot phase, is a useful approach to plan a comprehensive and meaningful evaluation later on. This article reports on the pilot results of an outcome evaluation of a complex mental health intervention and examines whether appropriate evaluation measures and indicators have been selected ahead of a clustered randomised control trial (cRCT). Methods The MENTUPP pilot is an evidence-based intervention for Small and Medium Enterprises (SMEs) active in three work sectors and nine countries. Based on our ToC, we selected the MENTUPP long-term outcomes, which are reported in this article, are measured with seven validated scales assessing mental wellbeing, burnout, depression, anxiety, stigma towards depression and anxiety, absenteeism and presenteeism. The pilot MENTUPP intervention assessment took place at baseline and at 6 months follow-up. Results In total, 25 SMEs were recruited in the MENTUPP pilot and 346 participants completed the validated scales at baseline and 96 at follow-up. Three long-term outcomes significantly improved at follow-up ( p < 0.05): mental wellbeing, symptoms of anxiety, and personal stigmatising attitudes towards depression and anxiety. Conclusions The results of this outcome evaluation suggest that MENTUPP has the potential to strengthen employees’ wellbeing and decrease anxiety symptoms and stigmatising attitudes. Additionally, this study demonstrates the utility of conducting pilot workplace interventions to assess whether appropriate measures and indicators have been selected. Based on the results, the intervention and the evaluation strategy have been optimised.